Restricted but satisfied: Google Maps and agency in the mundane life - Gentzel, Peter; Wimmer, Jeffrey (Convergence: The International Journal of Research into New Media Technologies, 2023)
The study grasps the transformation of agency in the context of mundane production and use of mapping apps. It is asked theoretically and empirically, who produces and maintains Google Maps as cartographic infrastructure and how is this kind of agency being reflected and acted upon from a lifeworld perspective. Firstly, findings are compiled from various interdisciplinary studies on digital cartography, platform capitalism and digital infrastructures. Since these studies focus on agency almost exclusively from a structural perspective, a qualitative study is conducted to explore the use of Google Maps in everyday life. 20 interviews with German users show that digitalization and datafication profoundly change the dynamics of how agency is perceived and reflected. It can be understood as a form of extension of agency because it is deeply rooted in the entanglement of Google Maps’ infrastructure and city dwellers everyday practices.<br
Keywords: Agency; appropriation; datafication; google maps; grounded theory; mediatization; qualitative interviews; platform studies; surveillance capitalism